Karakterisasi fisikokimia dan functional properties tepung kulit buah jeruk bali (Citrus maxima) dan tepung kulit buah nangka (Artocarpus heterophyllus) - Karina Natalie; Tjandra Pantjajani; Ardhia Deasy Rosita Dewi; Maria Goretti M. Purwanto (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2022)
Jackfruit and pomelo are tropical fruits that are popular among the people of Southeast Asia, including Indonesia because of their nutritional content such as carbohydrates, protein, minerals, and vitamins that are very beneficial for the health of the body. Jackfruit peel and pomelo peel are often just a waste and disposed of as organic waste. This study aims to compare the physical, chemical, and functional characteristics of jackfruit peel flour, pomelo peel flour, and wheat flour. The experimental design used was a completely randomized design with a variety of flour types. Based on the results of the physical test, the three types of flour gave significant differences in the color parameters. The kamba density value of jackfruit rind flour was not significantly different from that of wheat flour, while the kamba density value of pomelo rind flour was significantly different from that of wheat flour and jackfruit rind flour. Based on the results of chemical tests, the three types of flour differed significantly from each other in the content of ash, fat, crude fiber, protein, carbohydrates, pectin, and starch. The water content of pomelo peel flour was not significantly different from that of wheat flour. However, the water content of jackfruit rind flour was significantly different from that of wheat flour. Meanwhile, the ash content of pomelo peel flour and jackfruit peel flour were not significantly different from each other, but both were significantly different from wheat flour. Then for the functional parameters, OHC, swelling power, and solubility of the three flours were significantly different from each other. While the WHC of pomelo peel flour and jackfruit peel flour were not significantly different from each other, but the WHC values were significantly different from that of wheat flour.